Description and total ontogeny of the Sonoran Tiger Mantis, Stagmomantis clauseni sp. nov., and key to the subgenus Nigralora (Mantodea: Mantidae) - Garikipati, Lohitashwa (Zootaxa, 2024)
A recent reinvigorated effort into examining morphology and ecology of Nearctic Mantodea has led to the description of nearly 10 new species in the past decade. Expeditions to southern Arizona, combined with iNaturalist observations, suggested that S. wheelerii sensu Anderson is a complex of at least two cryptic species across its extensive range. Herein I describe one new species: Stagmomantis clauseni sp. nov., the Sonoran Tiger Mantis, from the Sonoran and Chihuahuan deserts, utilizing citizen science contributions, comparative morphology, and captive observations to describe its ontogeny and ethology. In addition, I also redescribe Stagmomantis wheelerii (Thomas 1875) and document the holotypes of Stagmomantis colorata (Hebard 1922) for the first time. The development of Stagmomantis clauseni sp. nov. also warranted the description of new hatching and signaling systems in Mantodea. For ease of both citizen and professional scientists a dichotomous key is provided for members of the subgenus Nigralora including characters in life.